Clinical Attributes and Electroencephalogram Analysis of Patients With Varying Alpers’ Syndrome Genotypes - Li, Hua; Wang, Wei; Han, Xiaodi; Zhang, Yujia; Dai, Lifang; Xu, Manting; Deng, Jie; Ding, Changhong; Wang, Xiaohui; Chen, Chunhong; Yang, Xiaofeng; Fang, Fang (Frontiers in Pharmacology, 2021)
Alpers’ syndrome is an early inceptive neurodegenerative disorder with a poor prognosis, characterized by developmental regression, intractable epilepsy, and hepatic dysfunction. Candidate genes, such as POLG, PARS2, CARS2, FARS2, NARS2, and GABRB2 are distinguished and registered following research on large cohorts that portray the clinical phenotype in such patients using expanded access to whole-exome sequencing (WES). In this study, we aimed to better understand the electroencephalogram (EEG) characteristics and clinical phenotype of different genotypes of the Alpers’ syndrome, which are currently insufficiently studied. We conducted a study on seven patients with Alpers’ syndrome who received treatment in Beijing Children’s Hospital and had a detailed clinical EEG. Furthermore, a substantial literature search of the Chinese Biomedical Literature Database, PubMed, and Cochrane Central Register of Controlled Trials EMBASE was also conducted, which revealed a total of 22 reported cases between January 2008 to January 2021. We analyzed 29 cases of Alpers’ syndrome caused by different gene variants, of which 22 cases were related to POLG gene mutation and 7 cases were related to PARS2, CARS2, FARS2, NARS2, and GABRB2 gene mutation, and found that patients with distinctive pathogenic variants exhibited comparable phenotypes and similar EEG patterns. And we defined EEG characteristics found specifically in Alpers’ syndrome. Rhythmic high-amplitude delta with superimposed (poly) spikes (RHADS) is a characteristic EEG finding in the early stages of Alpers’ syndrome and is a kind of epileptic phenomenon, which can provide clues for the early diagnosis of the disease.